2021
DOI: 10.1111/iwj.13726
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy compared with conventional wound dressings for closed incisions in orthopaedic trauma surgery: A meta‐analysis

Abstract: We performed a meta-analysis to evaluate the effect of negative pressure wound therapy compared with conventional wound dressings on closed incisions in orthopaedic trauma surgery. A systematic literature search up to October 2021 was done and 12 studies included 3555 subjects with closed incisions in orthopaedic trauma surgery at the start of the study: 1833 of them were provided with negative pressure wound therapy and 1722 were conventional wound dressings. They were reporting relationships about the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
(107 reference statements)
1
14
0
Order By: Relevance
“…Similarly, more studies are needed to deliver a clinically meaningful difference in the results. This was recommended also in preceding similar meta‐analysis studies which showed a similar influence of NPWT and conventional dressings in subjects with different types of OTS 30,45‐53 . Well‐conducted studies are also needed to evaluate these factors and the mixture of different ages, and ethnicity; since our meta‐analysis study could not answer whether they are linked to the results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, more studies are needed to deliver a clinically meaningful difference in the results. This was recommended also in preceding similar meta‐analysis studies which showed a similar influence of NPWT and conventional dressings in subjects with different types of OTS 30,45‐53 . Well‐conducted studies are also needed to evaluate these factors and the mixture of different ages, and ethnicity; since our meta‐analysis study could not answer whether they are linked to the results.…”
Section: Discussionmentioning
confidence: 95%
“…This was recommended also in preceding similar meta‐analysis studies which showed a similar influence of NPWT and conventional dressings in subjects with different types of OTS. 30 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 Well‐conducted studies are also needed to evaluate these factors and the mixture of different ages, and ethnicity; since our meta‐analysis study could not answer whether they are linked to the results. We suggest that well‐designed, high‐quality RCTs are needed to evaluate the effect of NPWT on closed incisions in OTS.…”
Section: Discussionmentioning
confidence: 99%
“…Wound therapy with NPWT was characterized by a significantly lower incidence of deep infection of the operated site and wound dehiscence compared to conventional methods using active dressings. The authors did not note a significant effect on the length of hospital stay compared to conventional methods [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies clearly indicate the usefulness of NPWT in the wound healing process [ 7 , 9 ] and, thus, for the method to be implemented in clinical practice it should be made known and available to professionals dealing with wound therapy. Reports and meta-analyses from recent years clearly indicate the advantages of NPWT and the increasing possibilities for its use in reducing the costs and risk of wound infection [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, ciN-PWT promotes healing by facilitating wound approximation, angiogenesis, and fluid management, and by decreasing bacterial load. 4 ciNPWT has been investigated in a variety of surgical specialties, [5][6][7][8][9] and its use continues to grow in breast reconstruction. A systematic review and meta-analysis recently demonstrated reduced overall wound complications and flap necrosis using ciN-PWT in implant-based breast reconstruction, and several reviews have shown benefit in primary wound closure.…”
Section: Introductionmentioning
confidence: 99%